PERFORMANCE TRAITS OF SAHIWAL AND JERSEY X SAHIWAL CROSSBREDS - REDDY, Y. RAVINDRA; RAO, K. SARJAN; BABU, D. SURESH; GANGARAJU, G. (Indian Journal of Animal Production and Management, 2017)
ABSTRACT The data of 60 lactation records and reproduction parameters of the Sahiwal and Jersey x Sahiwal crossbred cows maintained at Dairy Experimental station, College of Veterinary Science, Tirupati were utilized for the study. The average lactation milk yield, peak yield, average daily milk yield in Sahiwal cow were 1780 ± 5.40 kg, 9.20 ± 16 kg, 6.05 ± 0.06 kg respectively whereas in Jersey x Sahiwal cow the average lactation milk yield, peak yield and daily milk yield were 2984.51 ± 65.41 kg, 14.12 ± 0.18 and 10.25 ± 0.22 kg respectively. The days to attain peak yield and lactation length in Sahiwal cow and Jersey x Sahiwal cow were 38.32 ± 1.25, 295.54 ± 2.95 days and 42.23 ± 1.25, 285± 1.95 days respectively. The mean gestation period, dry period, service period and calving period (days) in Sahiwal and jersey x Sahiwal cows were 285.12 ± 0.63 days, 176.79 ± 8.12 days, 205.0 ± 3.27 days and 490 .58 ± 4.16 and 281.58 ±0.38 days , 128.52 ± 6.28, 152.0 ± 3.97 and 432.58 ± 5.10 respectively. The average Fat and SNF % in Sahiwal and Jersey x Sahiwal cows were 4.89 ± 0.15 , 9.01 ± 0.05 and 4.48 ± 0.18 , 8.62 ± 0.10 respectively. Key words: Lactation yield, Peak yield.